Thermal Diffusivity And Dielectric Properties Of Strontium- Doped Barium Titanate And Calsium Titanate Systems. - Ridha, Noor Jawad (2009)

(untitled)
In this thesis, the structure, thermal diffusivity and dielectric constant of Ba1-xSrxTiO3 and Ca1-xSrxTiO3 (0 ≤ x ≤ 1) ceramics were investigated. The samples were prepared using solid-state reaction technique with a sintering temperature at 1200 °C. From XRD analysis, the BaTiO3 structure obtained was tetragonal and then transformed to cubic; whilst, CaTiO3 structure changed from orthorhombic to cubic with an intermediate tetragonal phase as the amount of Sr ions increased. Surface morphology studies showed that the grain size decreased with increasing Sr ions in both Ba1-xSrxTiO3 and Ca1-xSrxTiO3 systems. Photoflash technique was used to determine the thermal diffusivity of BaTiO3, CaTiO3 and SrTiO3 at room temperature. The effect of substitution Sr ions on the thermal diffusivity of Ba1-xSrxTiO3 and Ca1-xSrxTiO3 was also investigated. It was found that increasing Sr ions in Ba1-xSrxTiO3 samples reduced the thermal diffusivity value from 11.302 × 10-3 cm2/s to 6.467 × 10-3 cm2/s and accompanying by a decrease in density. Similarly, the thermal diffusivity values of Ca1-xSrxTiO3 system decreased from 13.11 × 10-3 cm2/s to 6.467 × 10-3 cm2/s as its density increased. For thermal diffusivity measurement at higher temperature, laser flash technique was used. It was noticed that the thermal diffusivity of Ba1-xSrxTiO3 and Ca1-xSrxTiO3 decreased with increasing temperature from room temperature to 150 °C. The dielectric properties of BaTiO3, CaTiO3 and SrTiO3 were investigated at various temperatures from 25 to 150 °C using AC impedance analyzer. Increasing Sr ions in BaTiO3 reduced the dielectric constant from 709 to 246 at frequency 106 Hz at room temperature. On the other hand, increasing Sr ions in CaTiO3 raised the dielectric constant from 106 to 246, and the highest value was found at x = 0.2. The dielectric constant of Ba1-xSrxTiO3 decreased with increasing temperature. The highest dielectric constant value was recorded for Ba1-xSrxTiO3 system where x = 0 and 0.1 at phase change temperatures, 125 °C and 100 °C respectively.